Nutritional assessment of pre-school children in Anganwadi centres and to understand its association with various socio-demographic factors - Najiya; Roshni Gangan (International Journal of Contemporary Pediatrics, 2023)
Background: Malnutrition is clearly linked to inappropriate feeding practices rather than food availability or household food security. A proper diet is essential from early stages of life for growth and development. Methods: It was a cross-sectional study. Results: Eighty-six percentage of children had normal weight for age, while 8.6% had low weight for age. 5% of children were stunted. Female children, those living in joint family, those having more number of siblings, low educational qualification of parents and late weaning were associated with under nutrition and stunting. Conclusions: Results of the present study showed that the nutritional status of children in the studied population were better compared to other available studies and the national standards. <!--/data/user/0/com.samsung.android.app.notes/files/clipdata/clipdata_bodytext_230207_134633_108.sdocx-->